Identification of Delay Factor in Oman Construction Industry - Imran Latif, Qadir Bux alias; Al Saadi, Aysha Mehfoodh Dhiyab; Abdul Rahman, Ismail (International Journal of Sustainable Construction Engineering and Technology, 2019)
Construction industry is second most significant and largest industry in gulf countries that continuously and rapidly growing. However the decline in economies of gulf countries due to fluctuated oil has ambiguous effect on the construction industry. Like other countries around the world, construction industries in gulf region also facing many problems and amongst the most common problem is delay/time overrun. This paper aims to identify various factors in construction management which causing delay in construction projects at Muscat, Khabourah, Bidbid, Musanah and Sohar cities in OMAN. Fourty eight (48) delay factors identified from literature around the world and organized in structured questionnaire survey form. Delay factors were categorized into five major groups in construction process which are Planning, Design, Construction, Finishing, and Miscellaneous. The forms were distributed amongst the construction experts focusing clients, consultants and contractors involved in the construction projects. A total of 105 collected data were analyzed by using Average Index method for each factor. Furthermore, delay causing factors analyzed by individual response of client, consultant and contractor prospective. The analysis identified that ‘changes in scope of project’, ‘lack of communication between parties’, ‘shortage of skilled labour’, ‘mistakes during construction’, and ‘insufficient data collection and survey before designing’; are the most significant causes in each category respectively. The result of this study is useful to create or/and improve guideline considering delay, to avoid problems in looming construction.